2015
DOI: 10.1016/j.molmet.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

FTO is necessary for the induction of leptin resistance by high-fat feeding

Abstract: ObjectiveLoss of function FTO mutations significantly impact body composition in humans and mice, with Fto-deficient mice reported to resist the development of obesity in response to a high-fat diet (HFD). We aimed to further explore the interactions between FTO and HFD and determine if FTO can influence the adverse metabolic consequence of HFD.MethodsWe studied mice deficient in FTO in two well validated models of leptin resistance (HFD feeding and central palmitate injection) to determine how Fto genotype ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
2
21
1
Order By: Relevance
“…High-fat diet-induced obesity is attenuated and exaggerated in Fto-deficient mice and transgenic mice overexpressing FTO, respectively [23][24][25]. Contrary to these findings, other studies demonstrated that increased fat mass or percent body fat in mice lacking FTO [24,26,27]. These findings suggest that FTO plays a role in the regulation of whole body metabolism in mice.…”
Section: Biological Function Of Ftomentioning
confidence: 84%
“…High-fat diet-induced obesity is attenuated and exaggerated in Fto-deficient mice and transgenic mice overexpressing FTO, respectively [23][24][25]. Contrary to these findings, other studies demonstrated that increased fat mass or percent body fat in mice lacking FTO [24,26,27]. These findings suggest that FTO plays a role in the regulation of whole body metabolism in mice.…”
Section: Biological Function Of Ftomentioning
confidence: 84%
“…Finally, it is worth discussing that, although high-dose TNF␣ is often known as a cachectic cytokine in diseases like cancers and infections, low-dose TNF␣ in the hypothalamus at the level of obesity-associated inflammation has been implicated to reduce the sensitivity of leptin in the control of feeding (57,58). This effect of TNF␣ in decreasing leptin sensitivity in feeding is in contrast with its augmentation in the BP-raising effect of leptin.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms and pathways related to the development of leptin resistance have been described in the past [76,77] and new ones are continuously discovered. The phosphodiesterase-3B (PDE3B)-cAMP- and Akt-pathways of leptin signaling in the hypothalamus, the fat mass and obesity-related (FTO) gene, transient receptor potential vanilloid type (TRPV)-1 channel, 15-deoxy-Δ(12,14) -prostaglandin J2 (15d-PGJ2), estradiol (E2) and peroxisome proliferator-activated receptor γ (PPARγ) are some of the recently identified molecules/pathways to be involved in leptin’s resistance development in animal studies [78*,79*,80*,81*,82*,83*]. Although this new knowledge creates new pathways for understanding leptin resistance, these still need to be confirmed in humans.…”
Section: Typical Obesity and Leptin Resistancementioning
confidence: 99%